1994
DOI: 10.1007/bf01730368
|View full text |Cite
|
Sign up to set email alerts
|

The role of life events in different categories of preterm birth in a group of women with previous poor pregnancy outcome

Abstract: The aim of the present study was to determine whether mothers reporting more life events experience more preterm births following both complicated and uncomplicated pregnancies. A Life Events Inventory was administered prospectively to women at high risk for poor obstetric and neonatal outcomes who took part in the Pregnancy Home Visiting Program (PHVP), a randomized controlled trial of the effect of a programme of antenatal home visits by midwives on the incidence of preterm birth. This study took place in We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…Pregnancy-related anxiety at 28-30 weeks (but not at 18-20 weeks, and not state anxiety or general perceived stress) was modestly correlated with gestational length (β = -0.14, P < .05) but not with PTB (P = .09) [285], confirming previous findings [286]. Some adequately adjusted studies found no association between PTB and psychosocial stress [289], anxiety and depression [509], or stressful life events [284,302]. Eating fewer than 3 meals and 2 snacks / day (which may represent a stressful life style or the effect of starvation) was significantly associated with PPROM (aOR 1.9, CI 1.02-3.4, n = 2065), but not with PTB occurring after PTL with intact membranes (aOR 1.1, CI 0.6-1.9) [510].…”
Section: Psychosocial Stress and Ptbsupporting
confidence: 78%
See 1 more Smart Citation
“…Pregnancy-related anxiety at 28-30 weeks (but not at 18-20 weeks, and not state anxiety or general perceived stress) was modestly correlated with gestational length (β = -0.14, P < .05) but not with PTB (P = .09) [285], confirming previous findings [286]. Some adequately adjusted studies found no association between PTB and psychosocial stress [289], anxiety and depression [509], or stressful life events [284,302]. Eating fewer than 3 meals and 2 snacks / day (which may represent a stressful life style or the effect of starvation) was significantly associated with PPROM (aOR 1.9, CI 1.02-3.4, n = 2065), but not with PTB occurring after PTL with intact membranes (aOR 1.1, CI 0.6-1.9) [510].…”
Section: Psychosocial Stress and Ptbsupporting
confidence: 78%
“…Pregnancy-related anxiety OR=2 [284][285][286] Psychosocial stress OR=0-1.8 [287][288][289] Low job satisfaction OR=1.3 [290] Working >42/week OR=1.3 [290] Standing >6h/day OR=1.3 [290] Poor social environment [229] Paid work [229] Unfavourable working conditions (standing etc.) [230,284,290] Cumulative chronic stress?…”
Section: Current Pregnancymentioning
confidence: 98%
“…Some life‐event scales also incorporate measures of the individual’s response, such as stressfulness rating, which may reflect both event severity and host susceptibility. The evidence that stressful life events adversely affect gestational length or very low birthweight is modest, although recent studies provide more consistent evidence of a small effect 8 , 60 –66 . Although most studies evaluated only acute events, in three studies that reported associations between stressors and either preterm delivery 60 or very low birthweight 8 both acute and chronic stressors were assessed.…”
Section: Stressful Life Eventsmentioning
confidence: 99%
“…In ALSPAC, we used data collected from study mothers on over 40 different common and rare life events based on items suggested by Brown and Harris [23], Barnett et al [24] and Honnor et al [25] at 6 time points covering the prenatal period until 3 years after the child's birth. Details of the life event questions are available in Table S2.…”
Section: Methodsmentioning
confidence: 99%